Dampak Positif Fitokimia Quercetin Terhadap Penyakit Kardiovaskular: Literature Review - Khayrani Riastayanthi (STIKes Ibnu Sina Ajibarang, 2025)
Cardiovascular disease includes several heart and cardiovascular problems. One in three deaths in the world is caused by heart disease. Handling and preventing deaths from cardiovascular disease needs to be improved. Flavonoids are phytochemicals commonly found in plants. Quercetin is one of the most common flavonoids. Quercetin is also known to have potential as an alternative intervention for people with heart disease. Therefore, the positive impact of quercetin on cardiovascular disease needs to be reviewed. This article uses a literature review method by reviewing articles from the last ten years (2014–2024) through trusted websites. The results of the study show a link between quercetin, cardiovascular disease, and the dose administered. It can be concluded that quercetin has a strong antioxidant effect, which can overall overcome and prevent cardiovascular disease.